1998
DOI: 10.1002/(sici)1097-4636(19981215)42:4<597::aid-jbm16>3.0.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

Stability of plasma-polymerized allylamine films with sterilization by autoclaving

Abstract: The stability of plasma-polymerized allylamine films with autoclaving sterilization cycles was investigated. Polymerized films were deposited under pulsed plasma conditions using two different duty cycles to provide surfaces having different initial amino group concentrations. The film properties were analyzed by XPS and water contact angle measurements before and after autoclaving. The reactions of these surfaces with trifluoroacetic anhydride provided quantitation of the amino surface concentrations before a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
48
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(52 citation statements)
references
References 15 publications
4
48
0
Order By: Relevance
“…More details on the chemical composition and stability of plasma-generated polyallylamine films have recently been published. 17,18 Figure 3 shows C-V responses for PA1 and PA2. The high-frequency (HF) response for both PA1 and PA2 clearly shows accumulation and depletion regions that are typical in HF Si MOSFET characteristics.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…More details on the chemical composition and stability of plasma-generated polyallylamine films have recently been published. 17,18 Figure 3 shows C-V responses for PA1 and PA2. The high-frequency (HF) response for both PA1 and PA2 clearly shows accumulation and depletion regions that are typical in HF Si MOSFET characteristics.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…It can, thus, be concluded that the rfGD plasma treatment is the best technique for sterilizing polyester devices in tissue-engineering applications because it does not alter the three-dimensional morphology of the scaffolds. Calderon et al investigated the stability of plasma-polymerized allyamine films with an autoclaving sterilization cycle [149]. Polymerized films are deposited under pulsed plasma conditions using two duty cycles to give rise to surfaces having different initial amino group concentrations.…”
Section: Plasma Sterilizationmentioning
confidence: 99%
“…Like all the PE-CVD processes, the proposed approach has several advantages, e.g., it is solvent free and ecofriendly, it allows the deposition of strongly adhered pinhole-free polymer films on different substrates with several geometries or shapes, the treatment is performed at low temperature with minimal thermal stress, resistance to degradation and with the possibility to treat also thermolabile materials (e.g., paper, polymers, etc.) [14][15][16][17][18][19][20]. At the best of our knowledge, the co-deposition by PE-CVD of fluorocarbon and a carboxylic acid for the preparation of hydrophilic fluorinated polymer has never been reported.…”
Section: Introductionmentioning
confidence: 99%